Gurule enjoys big-budget work for bity of Albuquerque - Mullings, David (Raton Range Raton, New Mexico)
Newspaper article on Bob Gurule's big-budget for the City of Albuquerque, New Mexico.
Master list item #: 8
File location is in the Raton file Cabinet
Keywords: Gurule, Bob; Selvia, George; Hurley, Wilson; Shultz, Ken; Public Works Department; City of Raton; Albuquerque International Airport; Albuquerque Government; Local History; Biography; Budget; Mayor; City Budget; City Manager; Economy; Water Supply; Raton, New Mexico